Bridged PVDF / BaTiO3 composite nanofiber membrane and preparation method thereof

Through the preparation method of bridged PVDF/BaTiO3 composite nanofiber membrane, the problem of insufficient mechanical properties of existing piezoelectric materials is solved, and higher piezoelectric properties and mechanical properties are achieved, which is suitable for piezoelectric sensing equipment.

CN119736762APending Publication Date: 2025-04-01SHANDONG JIANZHU UNIV

Patent Information

Application Number
CN202411933686.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The mechanical properties of existing piezoelectric materials prepared by combining inorganic and organic materials are poor and cannot meet the needs of practical applications.

Method used

The preparation method of bridged PVDF/BaTiO3 composite nanofiber membrane is adopted, and the BaTiO3 nanofibers are bridged with PVDF fibers through electrospinning technology to form a composite nanofiber membrane with excellent piezoelectric properties.

Benefits of technology

The piezoelectric performance of the composite nanofiber membrane is improved, its mechanical properties are enhanced, and it can effectively transmit the bending piezoelectric effect caused by external forces, achieving higher voltage output.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736762A_ABST
    Figure CN119736762A_ABST
Patent Text Reader

Abstract

The invention provides a bridging type PVDF / BaTiO3 composite nanofiber membrane and a preparation method thereof.The preparation method of the fiber membrane includes the steps that BaTiO3 precursor sol and a PVDF solution are prepared respectively, and BaTiO3 nanofiber powder is obtained after the BaTiO3 precursor sol is subjected to electrostatic spinning, stepped high-temperature calcination and grinding; the preparation method comprises the following steps: mixing BaTiO3 nanofiber powder and a PVDF (Polyvinylidene Fluoride) solution to prepare PVDF / BaTiO3 precursor sol; and finally, carrying out electrostatic spinning to obtain the bridging type PVDF / BaTiO3 composite nanofiber membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano functional materials and relates to a bridged PVDF / BaTiO3 composite nano fiber membrane and a preparation method thereof. Background Art

[0002] With the rapid advancement of wearable electronic technology, its application in the field of biomedical health monitoring is becoming more and more extensive, and the demand for such devices is also growing. To meet these needs, it is key to develop solutions that are biocompatible, comfortable, and stably powered, while being able to continuously monitor physiological signals.

[0003] At present, the traditional battery power supply method is gradually becoming insufficient due to the limitations of battery capacity and life. In this context, flexible piezoelectric nanogenerators based on the piezoelectric effect have attracted widespread attention due to their self-powered ability, simplified design structure, light weight, high cost performance and miniaturization. Flexible piezoelectric nanogenerators can convert various human body movements, such as pulse beating, breathing, vocal cord vibration and limb movement, into electrical energy, providing a reliable and continuous power supply method for wearable electronic devices, and becoming an ideal choice for the development of flexible self-powered electronic devices.

[0004] In the research and development of piezoelectric materials, it has been confirmed that a variety of inorganic and organic materials can be used to manufacture piezoelectric nanosensors, including inorganic ceramics such as ZnO, BaTiO3, and lead zirconate titanate with good piezoelectric conversion performance. However, these inorganic ceramic materials are limited in their application in wearable electronic products due to their brittleness, rigidity, low mechanical impact resistance, and some toxicity. Organic piezoelectric polymers such as polyacrylonitrile (PAN) and polyvinylidene difluoride (PVDF) are increasingly valued due to their excellent mechanical flexibility, good biocompatibility with human skin, sensitivity to voltage changes, low impedance, and high mechanical flexibility. Studies have found that combining inorganic and organic materials can effectively improve the piezoelectric properties of PVDF, solve the problem of insufficient piezoelectric properties of pure PVDF films, and the composite piezoelectric film can meet the flexibility requirements, and the prepared electronic devices have good output stability. However, the mechanical properties of piezoelectric materials prepared by combining inorganic and organic materials are poor and cannot meet practical applications. Summary of the invention

[0005] The purpose of the present invention is to provide a bridged PVDF / BaTiO3 composite nanofiber membrane and a preparation method thereof, so as to solve the problem that the mechanical properties of the existing piezoelectric materials prepared by combining inorganic and organic materials are poor.

[0006] To achieve the above object, the present invention adopts the following technical solutions: The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane. The fiber membrane is first prepared by separately preparing a BaTiO3 precursor sol and a PVDF solution. The BaTiO3 precursor sol is subjected to electrospinning, step-by-step high-temperature calcination, and grinding to obtain a BaTiO3 nanofiber powder; the BaTiO3 nanofiber powder and the PVDF solution are mixed to prepare a PVDF / BaTiO3 precursor sol, and finally electrospinning is performed to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane.

[0007] Specifically, the preparation method of the bridged PVDF / BaTiO3 composite nanofiber membrane in the present application includes: S01: dissolving polyacetylacetonate titanium, barium acetate Ba(C2H3O2)2 and PVDF in a co-solvent respectively to form polyacetylacetonate titanium solution, Ba(C2H3O2)2 solution and PVDF solution.

[0008] Add titanium polyacetylacetonate to the cosolvent at a mass ratio of 1:3-5, and stir and dissolve at a temperature of 45-55°C for 2 hours to form a titanium polyacetylacetonate solution. Titanium polyacetylacetonate is a precursor for preparing BaTiO3 nanofibers. Preferably, the dissolution temperature of titanium polyacetylacetonate in the cosolvent is 55°C.

[0009] Ba(C2H3O2)2 is added to the co-solvent at a mass ratio of 1:2-3, and stirred and dissolved at a temperature of 45-55°C for 0.5h to form a barium acetate solution. Preferably, the dissolution temperature of BaTiO3 in the co-solvent is 55°C.

[0010] PVDF is added to the co-solvent at a mass ratio of 1:8-12, and stirred and dissolved at a temperature of 45-55°C for 2 hours to form a PVDF solution. Preferably, the dissolution temperature of PVDF in the co-solvent is 55°C.

[0011] The co-solvent in the present application is selected from one or more of anhydrous methanol, anhydrous ethanol, acetic acid, acetone, and N,N-dimethylformamide.

[0012] Preferably, anhydrous methanol is used to dissolve titanium polyacetylacetonate, acetic acid is used to dissolve Ba(C2H3O2)2, and acetone and N,N-dimethylformamide are used to dissolve PVDF. More preferably, the mass ratio of titanium polyacetylacetonate to anhydrous methanol is 1:4, the mass ratio of Ba(C2H3O2)2 to acetic acid is 1:2, and the mass ratio of PVDF, acetone and N,N-dimethylformamide is 1:3-5:5-7.

[0013] S02: slowly add the Ba(C2H3O2)2 solution into the polyacetylacetonate titanium solution, mix well, add PEO, stir well, and form a BaTiO3 precursor sol.

[0014] The Ba(C2H3O2)2 solution is slowly added to the polyacetylacetonate titanium solution and mixed evenly, wherein the molar ratio of polyacetylacetonate titanium to Ba(C2H3O2)2 is 1:1. After the Ba(C2H3O2)2 solution and the polyacetylacetonate titanium solution are mixed evenly, a spinning aid PEO (polyethylene oxide) is added, and the mixture is heated and stirred at 45-55°C for 3-5 hours to form a BaTiO3 precursor sol.

[0015] S03: The BaTiO3 precursor sol is subjected to electrostatic spinning, step-wise high-temperature calcination and grinding to obtain BaTiO3 nanofiber powder.

[0016] The BaTiO3 precursor sol is added to the stainless steel needle syringe of the spinning device, and electrostatic spinning is performed by high-voltage electrospinning to obtain a BaTiO3 precursor nanofiber membrane. The conditions for the electrostatic spinning of the BaTiO3 precursor sol are: temperature 20-35°C, relative humidity 30-70%, applied voltage 14-18kV, spinning solution flow rate 0.5-2.5ml / h, positive electrode stainless steel needle inner diameter 0.45-0.55mm, and the distance between the needle and the collecting fiber drum is 10-30cm. In the present application, aluminum foil is laid at the fiber collection part of the spinning device to facilitate the peeling of the BaTiO3 precursor nanofiber membrane.

[0017] The BaTiO3 precursor nanofiber membrane obtained by electrospinning was placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: in air, the temperature is increased from room temperature to 500-600°C at a heating rate of 1°C / min; then the temperature is increased to 700-750°C at a heating rate of 5°C / min; the temperature is stopped and kept warm for 2 hours.

[0018] During the high-temperature calcination process, the organic ligands in the BaTiO3 precursor nanofiber membrane will undergo oxidative decomposition and release gas. If the heating rate of the high-temperature calcination is too fast, a large amount of gas will be generated in a short period of time, destroying the structure of the BaTiO3 nanofiber. Therefore, in this application, a step-by-step heating method is used to calcine the BaTiO3 precursor nanofiber membrane at high temperature to prevent the decomposed gas from destroying the structure of the BaTiO3 nanofiber due to the too fast heating rate.

[0019] The BaTiO3 nanofibers obtained by high temperature calcination are ground into an agate mortar to form BaTiO3 nanofiber powder. In the present application, if the length of the BaTiO3 nanofiber powder is too short, a bridge-type structure cannot be formed; if the length of the BaTiO3 nanofiber powder is too long, it is easy to block the needle during the electrospinning process. Therefore, the length of the BaTiO3 nanofiber powder in the present application is 1-10 μm.

[0020] S04: Evenly mix the BaTiO3 nanofiber powder and the PVDF solution to obtain a PVDF / BaTiO3 precursor sol.

[0021] Add BaTiO3 nanofiber powder to PVDF solution and stir evenly to form PVDF / BaTiO3 precursor sol, wherein the mass ratio of PVDF to BaTiO3 nanofiber powder is 1-20:1.

[0022] S05: The PVDF / BaTiO3 precursor sol is subjected to electrostatic spinning to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane.

[0023] The PVDF / BaTiO3 precursor sol is added to the stainless steel needle syringe of the spinning device, and electrostatic spinning is performed by high-voltage electrospinning to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrostatic spinning of the PVDF / BaTiO3 precursor sol are: temperature 20-35°C, relative humidity 30-70%, applied voltage 14-18kV, spinning solution flow rate 0.5-1.5ml / h, positive electrode stainless steel needle inner diameter 0.45-0.55mm, and the distance between the needle and the collecting fiber drum is 10-30cm. In the present application, aluminum foil is laid at the fiber collection part of the spinning device to facilitate the bridged PVDF / BaTiO3 composite nanofiber membrane.

[0024] In addition, the present application also provides a bridged PVDF / BaTiO3 composite nanofiber membrane, which is prepared by the above method.

[0025] The bridged PVDF / BaTiO3 composite nanofiber membrane in the present application is a structure in which rod-shaped or fibrous nano-BaTiO3 is used as a bridge to connect PVDF fibers.

[0026] The present invention has the following beneficial effects: (1) The PVDF / BaTiO3 composite nanofiber membrane in the present application is a bridge-type structure in which rod-shaped or fibrous nano-BaTiO3 is used as a bridge to connect PVDF fibers. When an external force is applied, the PVDF fiber bends, which not only enables the PVDF fiber itself to generate a piezoelectric effect, but also can be more effectively transmitted to the BaTiO3 nanofiber, so that the BaTiO3 nanofiber generates a piezoelectric effect, thereby enhancing the piezoelectric properties of the composite nanofiber membrane.

[0027] (2) The PVDF / BaTiO3 composite nanofiber membrane in this application has excellent piezoelectric properties. 33 =26pC / N, the composite nanofiber membrane with a size of 2*2cm can reach a peak voltage of 150V when clapping, which can light up 100 commercial LED bulbs.

[0028] (3) In this application, PVDF / BaTiO3 composite nanofiber membrane is prepared by electrospinning, which has a short preparation cycle, low synthesis temperature, low cost, high efficiency, simple equipment and controllable process.

[0029] (4) The PVDF / BaTiO3 composite nanofiber membrane in this application has excellent properties such as light weight, small size, high softness, high elasticity, good strain tolerance, and high piezoelectric coefficient. It can be used in piezoelectric sensing devices and has broad application prospects in the field of flexible ceramic nanofiber material preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an optical photograph of the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in Example 1 of the present application; Figure 2 This is a SEM (scanning electron microscope) image of the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in Example 1 of the present application; Figure 3 Schematic diagram of the bridging structure of the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in Example 1 of the present application Figure 4 This is the XRD (X-ray diffraction) diagram of the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in Example 1 of the present application; Figure 5 This is a stress-strain curve diagram of the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in Example 1 of the present application; Figure 6This is a tapping voltage-time curve of the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further explained and illustrated by means of specific embodiments below.

[0032] Example 1 The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane, and the preparation method of the fiber membrane includes: S101: Mix 5g of titanium polyacetylacetonate with 10g of anhydrous methanol, stir and dissolve at 55°C for 2h to form a titanium polyacetylacetonate solution. Mix 5g of Ba(C2H3O2)2 with 10g of acetic acid, stir and dissolve at 55°C for 0.5h to form a Ba(C2H3O2)2 solution. Mix 3g of PVDF, 12g of acetone and 18g of N,N-dimethylformamide, stir and dissolve at 55°C for 2h to form a PVDF solution.

[0033] S102: Slowly add the BaTiO3 solution into the polyacetylacetonate titanium solution, mix well, add 0.05 g PEO, heat and stir at 55° C. for 1 h to form a BaTiO3 precursor sol.

[0034] S103: Add 10g of BaTiO3 precursor sol into the stainless steel needle syringe of the spinning device, and use high-voltage electrospinning to perform electrospinning to obtain BaTiO3 precursor nanofiber membrane. The conditions for electrospinning of BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 15kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 25#, and the distance between the needle and the collecting fiber drum is 20cm. The BaTiO3 precursor nanofiber membrane obtained by electrospinning is placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: under air conditions, the temperature is raised from room temperature to 600°C at a heating rate of 1°C / min; then the temperature is raised to 700°C at a heating rate of 5°C / min; and the temperature is kept for 2h after the heating is stopped. The BaTiO3 nanofibers obtained by high temperature calcination were ground in an agate mortar to form BaTiO3 nanofiber powders with a length of 10 μm.

[0035] S104: 3 g of BaTiO3 nanofiber powder is mixed with 15 g of PVDF solution, and stirred evenly to form a PVDF / BaTiO3 precursor sol.

[0036] S105: Add PVDF / BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, use high-voltage electrospinning method to perform electrospinning, and the released fiber is drawn and collected on the drum to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrospinning the PVDF / BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 17kV, spinning solution flow rate 0.9ml / h, positive electrode stainless steel needle model 23#, and the distance between the needle and the collecting fiber drum is 20cm.

[0037] Example 2 The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane, and the preparation method of the fiber membrane includes: S201: Mix 5g of titanium polyacetylacetonate with 10g of anhydrous methanol, stir and dissolve at 55°C for 2h to form a titanium polyacetylacetonate solution. Mix 5g of Ba(C2H3O2)2 with 10g of acetic acid, stir and dissolve at 55°C for 0.5h to form a Ba(C2H3O2)2 solution. Mix 3g of PVDF, 12g of acetone and 18g of N,N-dimethylformamide, stir and dissolve at 55°C for 2h to form a PVDF solution.

[0038] S202: Slowly add the BaTiO3 solution into the polyacetylacetonate titanium solution, mix well, add 0.05 g PEO, heat and stir at 50° C. for 4 h to form a BaTiO3 precursor sol.

[0039] S203: Add 10g of BaTiO3 precursor sol into the stainless steel needle syringe of the spinning device, and use high-voltage electrospinning to perform electrospinning to obtain BaTiO3 precursor nanofiber membrane. The conditions for electrospinning of BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 15kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 25#, and the distance between the needle and the collecting fiber drum is 20cm. The BaTiO3 precursor nanofiber membrane obtained by electrospinning is placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: under air conditions, the temperature is raised from room temperature to 600°C at a heating rate of 1°C / min; then the temperature is raised to 700°C at a heating rate of 5°C / min; and the temperature is kept for 2h after the heating is stopped. The BaTiO3 nanofibers obtained by high temperature calcination were ground in an agate mortar to form BaTiO3 nanofiber powders with a length of 8 μm.

[0040] S204: 1.5 g of BaTiO3 nanofiber powder is mixed with 15 g of PVDF solution, and stirred evenly to form a PVDF / BaTiO3 precursor sol.

[0041] S205: Add PVDF / BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, use high-voltage electrospinning method to perform electrospinning, and the released fiber is drawn and collected on the drum to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrospinning the PVDF / BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 17kV, spinning solution flow rate 0.9ml / h, positive electrode stainless steel needle model 23#, and the distance between the needle and the collecting fiber drum is 25cm.

[0042] Example 3 The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane, and the preparation method of the fiber membrane includes: S301: Mix 5g of titanium polyacetylacetonate with 10g of anhydrous methanol, stir and dissolve at 50°C for 2h to form a titanium polyacetylacetonate solution. Mix 5g of Ba(C2H3O2)2 with 10g of acetic acid, stir and dissolve at 50°C for 0.5h to form a Ba(C2H3O2)2 solution. Mix 3g of PVDF, 12g of acetone and 18g of N,N-dimethylformamide, stir and dissolve at 50°C for 2h to form a PVDF solution.

[0043] S302: Slowly add the Ba(C2H3O2)2 solution to the polyacetylacetonate titanium solution, mix well, add 0.05g PEO, heat and stir at 50°C for 4h to form a BaTiO3 precursor sol.

[0044] S303: Add 10g of BaTiO3 precursor sol into the stainless steel needle syringe of the spinning device, and use high-voltage electrospinning to perform electrospinning to obtain BaTiO3 precursor nanofiber membrane. The conditions for electrospinning of BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 15kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 25#, and the distance between the needle and the collecting fiber drum is 20cm. The BaTiO3 precursor nanofiber membrane obtained by electrospinning is placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: under air conditions, the temperature is raised from room temperature to 600°C at a heating rate of 1°C / min; then the temperature is raised to 700°C at a heating rate of 5°C / min; and the temperature is kept for 2h after the heating is stopped. The BaTiO3 nanofibers obtained by high temperature calcination were ground in an agate mortar to form BaTiO3 nanofiber powders with a length of 6 μm.

[0045] S304: 1 g of BaTiO3 nanofiber powder is mixed with 15 g of PVDF solution, and stirred evenly to form a PVDF / BaTiO3 precursor sol.

[0046] S305: Add the PVDF / BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, use the high-voltage electrospinning method to perform electrospinning, and the released fibers are drawn and collected on the drum to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrospinning the PVDF / BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 17kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 23#, and the distance between the needle and the collecting fiber drum is 25cm.

[0047] Example 4 The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane, and the preparation method of the fiber membrane includes: S401: Mix 5g of titanium polyacetylacetonate with 10g of anhydrous methanol, stir and dissolve at 55°C for 2h to form a titanium polyacetylacetonate solution. Mix 5g of Ba(C2H3O2)2 with 10g of acetic acid, stir and dissolve at 55°C for 0.5h to form a Ba(C2H3O2)2 solution. Mix 3g of PVDF, 12g of acetone and 18g of N,N-dimethylformamide, stir and dissolve at 55°C for 2h to form a PVDF solution.

[0048] S402: slowly add the BaTiO3 solution into the polyacetylacetonate titanium solution, mix well, add 0.05g PEO, heat and stir at 55°C for 1h to form a BaTiO3 precursor sol.

[0049] S403: Add 10g of BaTiO3 precursor sol into the stainless steel needle syringe of the spinning device, and use high-voltage electrospinning to perform electrospinning to obtain BaTiO3 precursor nanofiber membrane. The conditions for electrospinning of BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 15kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 25#, and the distance between the needle and the collecting fiber drum is 20cm. The BaTiO3 precursor nanofiber membrane obtained by electrospinning is placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: under air conditions, the temperature is raised from room temperature to 600°C at a heating rate of 1°C / min; then the temperature is raised to 700°C at a heating rate of 5°C / min; and the temperature is kept for 2h after the heating is stopped. The BaTiO3 nanofibers obtained by high temperature calcination were ground in an agate mortar to form BaTiO3 nanofiber powders with a length of 1 μm.

[0050] S404: 0.75 g of BaTiO3 nanofiber powder is mixed with 15 g of PVDF solution, and stirred evenly to form a PVDF / BaTiO3 precursor sol.

[0051] S405: Add the PVDF / BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, and perform electrostatic spinning by high-voltage electrostatic spinning. The released fibers are drawn and collected on the drum to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrostatic spinning of the PVDF / BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 17kV, spinning solution flow rate 0.9ml / h, positive electrode stainless steel needle model 23#, and the distance between the needle and the collecting fiber drum is 25cm.

[0052] Example 5 The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane, and the preparation method of the fiber membrane includes: S501: Mix 5g of titanium polyacetylacetonate with 10g of anhydrous methanol, stir and dissolve at 55°C for 2h to form a titanium polyacetylacetonate solution. Mix 5g of Ba(C2H3O2)2 with 10g of acetic acid, stir and dissolve at 55°C for 0.5h to form a Ba(C2H3O2)2 solution. Mix 3g of PVDF, 12g of acetone and 18g of N,N-dimethylformamide, stir and dissolve at 55°C for 2h to form a PVDF solution.

[0053] S502: Slowly add the BaTiO3 solution into the polyacetylacetonate titanium solution, mix well, add 0.05g PEO, heat and stir at 50°C for 4h to form a BaTiO3 precursor sol.

[0054] S503: Add 10g of BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, and use high-voltage electrospinning to perform electrospinning to obtain BaTiO3 precursor nanofiber membrane. The conditions for electrospinning of BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 15kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 25#, and the distance between the needle and the collecting fiber drum is 20cm. The BaTiO3 precursor nanofiber membrane obtained by electrospinning is placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: under air conditions, the temperature is raised from room temperature to 600°C at a heating rate of 1°C / min; then the temperature is raised to 700°C at a heating rate of 5°C / min; and the temperature is kept for 2h after the heating is stopped. The BaTiO3 nanofibers obtained by high temperature calcination were ground in an agate mortar to form BaTiO3 nanofiber powders with a length of 8 μm.

[0055] S504: 0.6 g of BaTiO3 nanofiber powder is mixed with 15 g of PVDF solution, and stirred evenly to form a PVDF / BaTiO3 precursor sol.

[0056] S505: Add the PVDF / BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, and perform electrostatic spinning by high-voltage electrospinning method. The released fibers are drawn and collected on the drum to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrostatic spinning of the PVDF / BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 17kV, spinning solution flow rate 0.9ml / h, positive electrode stainless steel needle model 23#, and the distance between the needle and the collecting fiber drum is 25cm.

[0057] Example 6 The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane, and the preparation method of the fiber membrane includes: S601: Mix 5g of titanium polyacetylacetonate with 10g of anhydrous methanol, stir and dissolve at 55°C for 2h to form a titanium polyacetylacetonate solution. Mix 5g of Ba(C2H3O2)2 with 10g of acetic acid, stir and dissolve at 55°C for 0.5h to form a Ba(C2H3O2)2 solution. Mix 3g of PVDF, 12g of acetone and 18g of N,N-dimethylformamide, stir and dissolve at 55°C for 2h to form a PVDF solution.

[0058] S602: Slowly add the BaTiO3 solution to the polyacetylacetonate titanium solution, mix well, add 0.05g PEO, heat and stir at 50°C for 4h to form a BaTiO3 precursor sol.

[0059] S603: Add 10g of BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, and use high-voltage electrospinning to perform electrospinning to obtain BaTiO3 precursor nanofiber membrane. The conditions for electrospinning of BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 15kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 25#, and the distance between the needle and the collecting fiber drum is 20cm. The BaTiO3 precursor nanofiber membrane obtained by electrospinning is placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: under air conditions, the temperature is raised from room temperature to 600°C at a heating rate of 1°C / min; then the temperature is raised to 700°C at a heating rate of 5°C / min; and the temperature is kept for 2h after the heating is stopped. The BaTiO3 nanofibers obtained by high temperature calcination were ground in an agate mortar to form BaTiO3 nanofiber powders with a length of 8 μm.

[0060] S604: 0.3 g of BaTiO3 nanofiber powder is mixed with 15 g of PVDF solution, and stirred evenly to form a PVDF / BaTiO3 precursor sol.

[0061] S605: Add PVDF / BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, use high-voltage electrospinning method to perform electrospinning, and the released fibers are drawn and collected on the drum to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrospinning the PVDF / BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 17kV, spinning solution flow rate 0.9ml / h, positive electrode stainless steel needle model 23#, and the distance between the needle and the collecting fiber drum is 25cm.

[0062] Example 7 The present application provides a bridged PVDF / BaTiO3 composite nanofiber membrane, and the preparation method of the fiber membrane includes: S701: Mix 5g of titanium polyacetylacetonate with 10g of anhydrous methanol, stir and dissolve at 55°C for 2h to form a titanium polyacetylacetonate solution. Mix 5g of Ba(C2H3O2)2 with 10g of acetic acid, stir and dissolve at 55°C for 0.5h to form a Ba(C2H3O2)2 solution. Mix 3g of PVDF, 12g of acetone and 18g of N,N-dimethylformamide, stir and dissolve at 55°C for 2h to form a PVDF solution.

[0063] S702: Slowly add the BaTiO3 solution to the polyacetylacetonate titanium solution, mix well, add 0.05 g PEO, heat and stir at 50° C. for 4 h to form a BaTiO3 precursor sol.

[0064] S703: Add 10g of BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, and use high-voltage electrospinning to perform electrospinning to obtain BaTiO3 precursor nanofiber membrane. The conditions for electrospinning of BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 15kV, spinning solution flow rate 1ml / h, positive electrode stainless steel needle model 25#, and the distance between the needle and the collecting fiber drum is 20cm. The BaTiO3 precursor nanofiber membrane obtained by electrospinning is placed in a muffle furnace for step-by-step high-temperature calcination to obtain BaTiO3 nanofibers. The step-by-step high-temperature calcination conditions are: under air conditions, the temperature is raised from room temperature to 600°C at a heating rate of 1°C / min; then the temperature is raised to 700°C at a heating rate of 5°C / min; and the temperature is kept for 2h after the heating is stopped. The BaTiO3 nanofibers obtained by high temperature calcination were ground in an agate mortar to form BaTiO3 nanofiber powders with a length of 8 μm.

[0065] S704: 0.15 g of BaTiO3 nanofiber powder is mixed with 15 g of PVDF solution, and stirred evenly to form a PVDF / BaTiO3 precursor sol.

[0066] S705: Add PVDF / BaTiO3 precursor sol to the stainless steel needle syringe of the spinning device, use high-voltage electrospinning method to perform electrospinning, and the released fibers are drawn and collected on the drum to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane. The conditions for electrospinning the PVDF / BaTiO3 precursor sol are: temperature 25°C, relative humidity 55%, applied voltage 17kV, spinning solution flow rate 0.9ml / h, positive electrode stainless steel needle model 23#, and the distance between the needle and the collecting fiber drum is 25cm.

[0067] In the present application, the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in Example 1 was taken as an example for real-object photography, SEM detection, XRD detection and knocking voltage test, and the attached Figure 1-6 .

[0068] By the attached Figure 1-3 It can be seen that the composite nanofiber membrane prepared in Example 1 of the present application is white and film-like, and the bridge in the composite nanofiber membrane is barium titanate, and the main fiber is polyvinylidene chloride.

[0069] By the attached Figure 4 It can be seen that in the XRD diagram of the composite nanofiber membrane prepared in Example 1 of the present application, the diffraction peaks at 22.1°, 31.5°, 38.8°, 45.1°, and 56.0° are the diffraction peaks of barium titanate, and the diffraction peak at 20.2° belongs to polyvinylidene fluoride, which indicates that barium titanate and polyvinylidene fluoride are simultaneously present in the composite nanofiber membrane prepared in Example 1 of the present application.

[0070] By the attached Figure 5 , 6 It can be seen that the tensile strength of the composite nanofiber membrane prepared in Example 1 of the present application can reach more than 4 MPa, the strain can reach more than 80%, and the corresponding voltage when tapped by a finger can reach 60V.

[0071] In addition, the examples of the present application also tested the tensile strength, piezoelectric constant, hand-clapping peak voltage of the 2*2cm composite nanofiber membrane, and the number of lit bulbs of the composite nanofiber membrane prepared in Examples 1-7, and obtained Table 1.

[0072] Table 1: Performance test results of the composite nanofiber membranes prepared in Examples 1-7 As can be seen from Table 1, as the mass ratio of BaTiO3 nanofiber powder to PVDF continues to increase, the tensile strength of the bridged PVDF / BaTiO3 composite nanofiber membrane prepared in the embodiment of the present application continues to increase, with a minimum of 3.4MPa; the piezoelectric constant, peak voltage and the number of LED bulbs lit all increase first and then decrease, and the piezoelectric constant is 16-26 pC / N, the hand-clapping peak voltage of the composite nanofiber membrane with a size of 2*2cm is 40-150V, and the number of commercial LED bulbs lit reaches 30-100. Among them, when the mass ratio of BaTiO3 nanofiber powder to PVDF is 1:3, the performance of the prepared bridged PVDF / BaTiO3 composite nanofiber membrane is the best.

[0073] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a bridged PVDF / BaTiO3 composite nanofiber membrane, characterized in that: include: dissolving polyacetylacetonate titanium, Ba(C2H3O2)2 and PVDF in a co-solvent respectively to form polyacetylacetonate titanium solution, barium acetate solution and PVDF solution; Slowly adding the barium acetate solution to the polyacetylacetonate titanium solution, adding PEO after mixing evenly, stirring evenly to form a BaTiO3 precursor sol; The BaTiO3 precursor sol is subjected to electrostatic spinning, step-wise high-temperature calcination, and grinding to obtain BaTiO3 nanofiber powder; The BaTiO3 nanofiber powder and the PVDF solution are mixed evenly to obtain a PVDF / BaTiO3 precursor sol; The PVDF / BaTiO3 precursor sol is subjected to electrostatic spinning to obtain a bridged PVDF / BaTiO3 composite nanofiber membrane.

2. The method for preparing the bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 1, characterized in that: The molar ratio of the polyacetylacetonate titanium to the Ba(C2H3O2)2 is 1:

1.

3. The method for preparing the bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 1, characterized in that: The mass ratio of the polyacetylacetonate titanium to the co-solvent is 1:3-5, the mass ratio of the Ba(C2H3O2)2 to the co-solvent is 1:2-3, and the mass ratio of the PVDF to the co-solvent is 1:8-12.

4. The method for preparing the bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 1, characterized in that: The conditions for the electrospinning of the BaTiO3 precursor sol are: temperature 20-35°C, relative humidity 30-70%, applied voltage 14-18kV, spinning solution flow rate 0.5-2.5ml / h, positive electrode stainless steel needle inner diameter 0.45-0.55mm, and a distance between the needle and the collecting fiber drum of 10-30cm.

5. The method for preparing the bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 1, characterized in that: The step-by-step high-temperature calcination conditions are: in air conditions, heating from room temperature to 500-600°C at a heating rate of 1°C / min; then heating to 700-750°C at a heating rate of 5°C / min; and keeping warm for 2 hours after stopping heating.

6. The method for preparing the bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 1, characterized in that: The mass ratio of the PVDF to the BaTiO3 nanofiber powder is 1-20:

1.

7. The method for preparing a bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 1, characterized in that: The conditions for electrospinning the PVDF / BaTiO3 precursor sol are: temperature 20-35°C, relative humidity 30-70%, applied voltage 14-18kV, spinning solution flow rate 0.5-1.5ml / h, positive electrode stainless steel needle inner diameter 0.45-0.55mm, and a distance between the needle and the collecting fiber drum of 10-30cm.

8. The method for preparing a bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 1, characterized in that: The co-solvent is selected from one or more of anhydrous methanol, anhydrous ethanol, acetic acid, acetone, and N,N-dimethylformamide.

9. A bridged PVDF / BaTiO3 composite nanofiber membrane prepared by any one of the preparation methods of claims 1-8.

10. The bridged PVDF / BaTiO3 composite nanofiber membrane according to claim 9, characterized in that: The fiber membrane is a structure in which rod-shaped or fiber-shaped nano BaTiO3 is used as a bridge to connect PVDF fibers.

Citation Information

Patent Citations

  • Preparation method of polyvinylidene fluoride composite material with high piezoelectricity

    CN108221175A

  • Preparation method of flexible barium titanate ceramic nanofiber membrane

    CN110512354A

  • Preparation method of mixed phase change titanium dioxide regulated polyvinylidene fluoride nanofiber membrane

    CN114507942A

  • Ceramic material of composite nanosheet structure with barium titanate fiber surface coated with hexagonal boron nitride as well as preparation method and application of ceramic material

    CN117488437A

  • Preparation method and catalytic sterilization application of DA-Ag-BCZT / PVDF flexible piezoelectric composite fiber film

    CN118407192A

Cited By

  • Nanometer composite film as well as preparation method and application thereof

    CN120505752A